Genetic Regulation of the Thymic Stromal Lymphopoietin (TSLP)/TSLP Receptor (TSLPR) Gene Expression and Influence of Epistatic Interactions Between IL-33 and the TSLP/TSLPR Axis on Risk of Coronary Artery Disease - Nie, Shao-Fang; Zha, Ling-Feng; Fan, Qian; Liao, Yu-Hua; Zhang, Hong-Song; Chen, Qian-Wen; Wang, Fan; Tang, Ting-Ting; Xia, Ni; Xu, Cheng-Qi; Zhang, Jiao-Yue; Lu, Yu-Zhi; et al. (Frontiers in Immunology, 2018)
The thymic stromal lymphopoietin (TSLP)/TSLP receptor axis is involved in multiple inflammatory immune diseases, including coronary artery disease (CAD). To explore the causal relationship between this axis and CAD, we performed a three-stage case-control association analysis with 3628 CAD cases and 3776 controls using common variants in the genes TSLP, interleukin 7 receptor (IL7R), and TSLP receptor (TSLPR). Three common variants in the TSLP/TSLP receptor axis were significantly associated with CAD in a Chinese Han population (rs3806933T in TSLP, Padj=4.35×10-5, OR=1.18; rs6897932T in IL7R, Padj=1.13×10-7, OR=1.31; g.19646A>GA in TSLPR, Padj=2.04×10-6, OR=1.20). Reporter gene analysis demonstrated that rs3806933 and rs6897932 could influence TSLP and IL7R expression, respectively. Furthermore, the “T” allele of rs3806933 might increase plasma TSLP levels (R2=0.175, P<0.01). In a stepwise procedure, the risk for CAD increased by nearly 5-fold compared with the maximum effect of any single variant (Padj=6.99×10-4, OR=4.85). In addition, the epistatic interaction between TSLP and IL33 produced a nearly 3-fold increase in the risk of CAD in the combined model of rs3806933TT-rs7025417TT (Padj=3.67×10-4, OR=2.98). Our study illustrates that the TSLP/TSLPR axis might be involved in the pathogenesis of CAD through up-regulation of mRNA or protein expression of the referenced genes and might have additive effects on the CAD risk when combined with IL-33 signaling.